The Abraham Accords: Can Interculturalism Solve Grave Conflicts of the Middle East? - Karataş, İbrahim; Uslu, Nasuh (JOURNAL ECUMENICAL STUDIES, 2022)
The Abraham Accords are intended to end the still-unresolved Arab-Israeli conflict. Introduced also as an intercultural project to ensure peace among hostile countries of the Middle East, the Accords have been welcomed by some Arab states. This study analyzes the Abraham Accords and contends that, though their intercultural aspect is weak, they can still provide an opportunity for perpetual peace between Muslim Arabs and Jewish Israelis. If used as leverage, the Accords can also help resolve the Israeli-Palestinian conflict, but, if the Palestinian question is ignored, they may cause more radicalization among Palestinians. Further, the Accords have the potential to spark an intracultural conflict among Muslim countries unless they are not turned into a strong alliance that is also welcomed by Arabic public opinion.